A whole-cell immobilization system on bacterial cellulose for the paracetamol-degrading Pseudomonas moorei KB4 strain. (April 2020) - Żur, Joanna; Piński, Artur; Michalska, Justyna; Hupert-Kocurek, Katarzyna; Nowak, Agnieszka; Wojcieszyńska, Danuta; Guzik, Urszula
Abstract: Microorganisms with a high natural ability to degrade xenobiotics, which are usually characterized by a diverse metabolism and unique features, can be used as natural biocatalysts in wastewater treatment or bioaugmentation processes. The immobilization of such strains greatly increases their stability and degradation properties. The most critical issues in designing whole-cell immobilization systems are selecting the suitable carrier and determining the bacterial features that will promote effective immobilization. In this study, we immobilized the paracetamol-degrading Pseudomonas moorei KB4 strain on the bacterial cellulose disks that were produced by Komagataeibacter xylinus E-89370. The KB4 strain immobilized on the cellulose degraded 150 mg L −1 of paracetamol in three series of 50 mg L −1 in each cycle. The average protein concentration and dehydrogenase activity increased after the degradation of each dose. The specific activity (U mg −1 of protein) of the main enzymes involved in the degradation pathway was 0.22 for deaminase, 5.1 for acylamidohydrolase and 3.49 for ring-cleavage hydroquinone 1, 2-dioxygenase. The relative expression level of the genes encoding deaminases and acylamidohydrolases increased in the presence of paracetamol, though more prominently in the immobilized than in the free cells. Graphical abstract: Image 1 Highlights: Pseudomonas moorei KB4 exhibits the most critical traits for immobilization. Immobilized KB4 strain degrades 150 mg L −1 of paracetamol. Immobilized cells transform paracetamol via p -aminophenol and hydroquinone. Paracetamol exposure up-regulated expression of genes encoded degradative enzymes.